Identificação de oportunidades de melhoria no processo de precificação na área de controladoria com análise do efeito e modo de falhas (FMEA) - Oliveira, Shiley Kelly Andrade de (2024)
This work explored the application of Failure Mode and Effect Analysis (FMEA) to identify opportunities for process improvement in the pricing activity in a controlling area. The main objective of the research was to find improvements in execution throughout the pricing process. The action research methodology was used as a theoretical basis, which helped to structure and carry out the study. The research involved a detailed analysis of the existing process, identifying faults and proposing improvements with the support of quality tools and the FMEA, which was used to identify the main faults and prioritize actions. The results indicated that these tools were essential for optimizing the pricing process, offering practical and effective solutions to the problems identified. The study thus contributed to improving the quality of pricing activities in the controllership area.